Trends in occupational-related open globe injury presenting to a tertiary referral centre of Northern Thailand. Issue 9 (September 2020) - Patikulsila, Direk; Choovuthayakorn, Janejit; Supreeyathitikul, Pongsant; Chaovisitsaree, Thanaphat; Chaikitmongkol, Voraporn; Watanachai, Nawat; Kunavisarut, Paradee
Abstract: Purpose: To determine characteristics of occupational-related open globe injury (OGI) in a tertiary referral centre within an agricultural activity endemic area. Methods: The medical records of patients diagnosed as open globe injury received during work and admitted to Chiang Mai University Hospital, Thailand from January 2006 to December 2016, were retrospectively reviewed. Results: Six hundred and fifteen patients were included in this analysis with a mean (SD) age of 44.6 (14.1) years and a median (IQR) follow-up of 6.5 (2.5 to 17) months. Males were predominant (92%). The highest risk groups were patients in the age range of 40 to 59 years (52%). The common locations of injuries were gardening/farming (52%) followed by work at construction/industrial site (32%). Over the study period, there was an increasing proportion of intraocular foreign body (IOFB), while the proportion of penetrating injuries decreased ( p  = 0.001). An increasing frequency of injuries from mowing were noted ( p  = 0.003). Types of injury also varied in different working settings as follows: while higher proportion of penetrating OGI occurred at the office (86%), IOFB occurred more frequently at gardening/farming site (59%). Work setting did not influence either the initial visual acuity (VA) ( p  = 0.53) or the final VA ( p  = 0.73). Significant improvements in final VA were demonstrated across all work settings, but 46% of patients still had a final visual acuity worse than 20/400. Conclusions: The majority of occupational-related OGI in this study were related to agricultural work. A high incidence of injuries during mowing and a high frequency of IOFB should be considered when discussing guidelines and public recognition should be raised regarding safety protective measures at work.